MODEL SURPLUS PRODUKSI PENGELOLAAN IKAN TERI DI PERAIRAN SUNGAI APIT KABUPATEN SIAK PROVINSI RIAU - Zulkarnaini Zulkarnaini; Hazmi Arief; Zuriati Murni (Jurnal Ilmu Lingkungan, 2022)
Anchovies (Stolephorus sp), need to be managed well because although as a natural resource that is open access if not managed properly, the management of fishery resources is not optimal and sustainable. One approach in the management of fish resources is with a surplus production model. The analysis was conducted to obtain the best model that aims to know the maximum sustainable catch (MSY), utilization rate, and use of anchovies. Data on catches and anchovies fishing efforts were collected from the Siak District Fisheries and Livestock Service. The best Surplus Production Model used to assess the potential of anchovies is the Walter-Hilborn model. Optimal effort (EMSY) of 150 Units per year. Cmsy's optimal catch is 247.75 tons per year. The utilization rate for 2020 is 70%, with an entrepreneurial rate of 41%, which indicates that overfishing has not occurred both biologically and economically.